تطبيق الطريقة الاستجابة الجسدية الكلية(Total Physical Response) لحفظ المفرداة في المدراسة الإبتدائية الإسلامية مفتاح العلوم غراتي لوماجانج - Annazilah, Lailatul Munawaroh (Maliki Interdisciplinary Journal, 2024)
Vocabulary is one of the language elements that learners of foreign languages, including Arabic, must have. In memorizing and understanding vocabulary, appropriate methods or techniques are needed, so that ease and effectiveness in understanding vocabulary can be achieved. If this is not achieved, the process of memorizing and understanding vocabulary will become monotonous and tedious. Especially if the learning goal is the third grade level in elementary school. Learning Arabic for Islamic primary school level students requires teachers to always be creative and innovative in the learning process. Teaching Arabic to children requires more effort, because they have their own characteristics and uniqueness in learning the language. One of the child-friendly Arabic learning methods is TPR. (Total Physical Response) is a way to teach Arabic to children. The approach used is quantitative using experimental research. While the data collection method used the method of pretest and post test with kausal (parametric) analysis, i.e. Paired sample T test. To establish whether this research is significant, the researchers use SPSS (Statistical Package for the Social Sciences) data. The results of these data proved that there is an effect of the Total Ph response method (TPR) on vocabulary memorization in the Islamic primary school Miftahul Ulum Grati Lumajang. By using this method, students become more active and effective in learning Arabic subjects.